2019
DOI: 10.18280/ijht.370310
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Sinusoidal Profile in Fins on Thermal Performance

Abstract: The aim of the present study is to investigate the effect of using sinusoidal profile in fins on temperature distribution and heat transfer enhancement. The longitudinal fins of rectangular, triangular, wavy rectangular and wavy triangular profiles are studied using analytical and numerical solution techniques. In addition to known profiles, wavy triangular longitudinal fins are proposed as a new fin configuration. The temperature distribution of wavy triangular fins is obtained using Shooting Method along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The solution of B is computed by equation (20) where, the M-P pseudo inverse is represented by + M .…”
Section: Extreme Learning Machinementioning
confidence: 99%
See 1 more Smart Citation
“…The solution of B is computed by equation (20) where, the M-P pseudo inverse is represented by + M .…”
Section: Extreme Learning Machinementioning
confidence: 99%
“…Fins are practical apparatuses to dissipate heat from other electrical components, including computer processors and are significant in heat transfer applications such as heat evaporators, compressors, and internal combustion engines. Using the Runge-Kutta approach, Sertel and Bilen [20] studied heat transfer in a longitudinal fin. The analytical solution for a radiative rectangular fin was discussed by Gouran et al [21] with the aid of LSM and they discussed the radiative heat transfer mechanism in the fin.…”
Section: Introductionmentioning
confidence: 99%
“…They discovered the effect of Rayleigh number, fin lengths and fin positions on the flow structure and heat transfer behaviors. Sertel and Bilen [13] reported the effect of using sinusoidal profile in fins on thermal performance. They found that the heat transfer augmentation can be provided for wavy triangular fins at higher amplitude lengths.…”
Section: A Amplitudementioning
confidence: 99%
“…Furthermore, most of the research works were based on the experimental investigation of the heat transfer of fin-and-tube and plate-fin heat exchangers with wavy fins [29][30][31][32][33][34]. However, the studies of Sertel and Bilen [35] and Khaled [36] discuss the various types of wavy fins to recognize the thermal augmentation attributes. In particular, Khaled [36] studied the thermal variation in the wavy fin with constant thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%